Pembaharuan Hukum Acara Pidana Melalui Mekanisme Afdoening Buiten Process - Handoko, Priyo (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
Law of Criminal procedure is a framework for law enforcement officers to carry out law enforcing duties in enforcing the law, which contained in the Criminal Procedure Code. In its development, reforms needed in the Criminal Procedure Code. One of which is by adopting a mechanism or provisions for the settlement of cases out of court or Alternative Dispute Resolution (afdoening issuer process). This article aims to examine the significance of reform in the penal system in Indonesia. Through the spirit of actualising justice, usefulness, and legal certainty in criminal law, the author tries to describe the systematic problems of punishment in Indonesia. Also, the author uses several approaches, including a statutory, a conceptual, and a case approach. The results of the study reveal that the Indonesian criminal system enriched with corporal punishment. As the purpose of punishment adopted by the Indonesian is a combination of distributive theory and utilitarian theory, the emergence of Prosecutor's Regulation Number 15 of 2020 concerning Cessation of criminal Prosecution Based on Restorative Justice is the practical strategy to produce justice, benefit and legal certainty.